Perdas de solo e água por erosão hídrica em sistemas de culturas oleaginosas - Guth, Paulo Luis (2010)
The sustainability of vegetable oils production is in the dependence of the agricultural practices, being the erosion the most preoccupying form of soil degradation. In this way, was carried out a study in the UFSM campus, city of Santa Maria, between October of 2007 and October of 2009, with the objective to evaluate the soil and water losses by water erosion in systems of rotation of oleaginous crops and covering plants. The region climate is "Cfa" type, with 1686 mm annual medium precipitation. The soil with steepness of 6.5% is classified as Argissolo Vermelho distrófico arênico. The experimental unit is constituted of plots with dimensions of 3 m of width and 15 m of length. The experimental design is entirely random, with two repetitions. The treatments consist of three rotations: R1 (soybean, black oat/vetch, castor bean/peanut and canola), R2 (castor bean/peanut, oilseed radish, sunflower and black oat/vetch) and R3 (sunflower, canola, soybean and oilseed radish). Was determined the dry mass yield of summer and winter crops, and the grains yield of the oleaginous summer crops. Was done the sampling and measurement of runoff of each rain, being the soil and water losses calculated using the software Excel. The results of soil losses were expressed in kg ha-1 and the water losses in percent in relation to the rain. The erosivity index (EI30, MJ mm ha-1 h-1) was determined with the software Chuveros, from which was obtained the accumulated erosivity for each period of the crops. Was also proceeded the physical characterization (Dp, Ds, Pt, macro and microporosity, DMG, DMP and distribution of the aggregates size in water), in the depths of 0-8 and 8-16 cm, and chemistry (organic matter, macro and micronutrients) in the depths of 0-5 and 5-20 cm. To the obtained values, the test of Tukey was applied for comparison of the treatments averages. It is observed that canola, when compared to others wintrer crops, showed a significant decrease in dry mass in 2008 winter (R3) and also in winter of 2009 (R1). It is verified that are greater the productivity of grains of the crops of R2 (summer 2007/06) and R1 (summer 2008/09), both constituted by the consortium among castor bean/peanut, elevating significantly the total of grains produced in this consortium, comparing to single crop of soybean and sunflower. It is verified in 2009, a tendency of decrease of Ds, DMP and larger aggregates, favoring the minor classes. The alterations in the chemical characteristics can be attributed to the application of lime and the modifications in the tenors of organic matter that happen in depth. The soil and water losses increase in the measure in that it decreases to dry mass added by the crops. Even if is considered R3, where it was obtained the largest soil losses (4641 kg ha-1) and water (23.33%), it is observed that the values obtained in this work are low. Soybean and sunflower grain yield is significantly smaller than the consortiated castor bean and peanut crops.